2017
DOI: 10.1186/s12883-017-0900-8
|View full text |Cite
|
Sign up to set email alerts
|

Thrombocytopenia induced by dabigatran: two case reports

Abstract: BackgroundVitamin K inhibitors (e.g. warfarin) and indirect thrombin inhibitors (e.g. heparin) are widely used to prevent thromboembolic disorders (e.g. myocardial infarction, venous thromboembolism, and stroke). These agents have been mainstays of anticoagulation for people older than 60 years. However, their administration is associated with a risk of bleeding and requires careful monitoring of patients. Novel oral anticoagulants (NOACs), such as dabigatran, are significantly safer in preventing thromboembol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 17 publications
0
3
0
2
Order By: Relevance
“…9 cases of the 11 occurred following dabigatran therapy, and 2 cases occurred after rivaroxaban therapy. [18][19][20][21] None of these case reports provided a possible explanation or pathophysiological mechanism by which DOACs could cause thrombocytopenia.…”
Section: Discussionmentioning
confidence: 97%
“…9 cases of the 11 occurred following dabigatran therapy, and 2 cases occurred after rivaroxaban therapy. [18][19][20][21] None of these case reports provided a possible explanation or pathophysiological mechanism by which DOACs could cause thrombocytopenia.…”
Section: Discussionmentioning
confidence: 97%
“…In 2013, the nonheparin based oral anticoagulant drugs dabigatran, apixaban, edoxaban, and rivaroxaban were approved for clinical use . However, the side effects of these drugs clearly indicated that the use of classical heparin-based anticoagulants is still important for the antithrombotic therapy …”
Section: Discussionmentioning
confidence: 99%
“…Тем более, что ТП в инструкциях к ПОАК указана как редкая побочная реакция с частотой развития от ≥1/1000 до <1/100 пациентов. При этом единичные случаи ТП всё же были зарегистрированы и описаны как в зарубежной, так и в отечественной литературе [16][17][18]. В частности, в статье Татарского Б. А. и др.…”
Section: клиника и фармакотерапияunclassified